La pregunta por la pregunta - Camino Macedo, Federico (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
With Heidegger, the detailed study of what it is and what questioning implies begins in the history of philosophy, since, with the exceptions of Plato and Aristotle and possibly Descartes, a question as such was neglected, despite the fact that it is in the field of philosophy that questioning achieves its maximum fulfillment. The reflections of this article study the links between Érōs and the question (erṓtēsis), an essential connection that, although it is not etymo-logical but phonetical, allows us to find the common amphibian structure that joins together these two dimensions and makes it possible to establish an essen-tial link between Érōs as the strength and the question as the place where that strength is expressed, what is nothing other than philosophy as love or aspiration to knowledge.In the question-answer unit is that knowledge as a unit of what is sought and what is found.The question, a kind of symbol that links together, supposes a distancing that eliminates the immediacy of what is given and establishes a distance in which what is questioned and its aspiration to the unity of knowledge are placed. The question is the piety of thought, as Heidegger says, and the philosophical ques-tions, the expression of our first and last perplexities.

Con Heidegger se inicia en la historia de la filosofía el estudio pormenorizado de lo que es y lo que implica el preguntar, pues, con las excepciones de Platón y Aristóteles y posiblemente de Descartes, la pregunta como tal fue desatendida, a pesar de que es en la filosofía que el preguntar logra su máxima plenitud. Las reflexiones del presente artículo estudian las vinculaciones entre el Érōs y la pregunta (erṓtēsis), vinculación esencial que, si bien no es etimológica sino fonética, permite encontrar una común estructura anfibológica que une esas dos dimensiones y posibilita establecer un vínculo esencial entre el Érōs como fuerza y la pregunta como el lugar en que esa fuerza se expresa, lo que no es otra cosa que la filosofía en tanto amor o aspiración al saber. En la unidad pregunta-respuesta está ese saber como unidad de lo buscado y lo encontrado.La pregunta, suerte de símbolo que une, supone un distanciamiento que elimina la inmediatez de lo dado y establece una distancia en la que se sitúa lo interrogado y su aspiración a la unidad del saber. La pregunta es la piedad del pensamiento, como dice Heidegger, y las preguntas filosóficas, la expresión de nuestras primeras y últimas perplejidades.
The Inquiry for the Question
Keywords: Érōs; Question and questioning; Response; Symbol; Problem; Érōs; Pregunta y preguntar; Respuesta; Símbolo; Problema; https://purl.org/pe-repo/ocde/ford#6.03.01